Feeding activity rhythm in Japanese sea catfish Plotosus japonicus - Kasai, M.(Kagoshima Univ. (Japan)); Yamamoto, T; Kitasako, K; Kiyohara, S (Fisheries science, 2009)
To examine the feeding activity characteristics of Japanese sea catfish Plotosus japonicus, access to feed box (feeding activity) and the number of food pellets consumed (food intake) were recorded under laboratory conditions. When fed ad libitum under a 12:12 h light-dark (LD) cycle, all fish exhibited feeding activity and consumed food during the dark period. Feeding activity increased in the presence of food, and this increased activity level continued for several days after food removal. During restricted food availability within the light period of the LD cycle, seven of nine fish exhibited food-anticipatory activity (FAA) both before and after the 12:00 food-restricted time. This FAA persisted under constant light conditions (in nine of nine fish). The average circadian free-running period was 24 h. These results suggest that P. japonicus exhibits a nocturnal feeding activity rhythm, which may be synchronized by a food-restricted time.